2017
DOI: 10.1371/journal.pone.0169876
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Hot Red Chili Pepper Consumption and Mortality: A Large Population-Based Cohort Study

Abstract: The evidence base for the health effects of spice consumption is insufficient, with only one large population-based study and no reports from Europe or North America. Our objective was to analyze the association between consumption of hot red chili peppers and mortality, using a population-based prospective cohort from the National Health and Nutritional Examination Survey (NHANES) III, a representative sample of US noninstitutionalized adults, in which participants were surveyed from 1988 to 1994. The frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 30 publications
(28 reference statements)
4
49
0
2
Order By: Relevance
“…The phytochemical profile of this spice is characterized by the presence of molecules belonging to several chemical groups, acknowledged for their antioxidant activity (Zhuang, Chen, Sun, & Cao, ), with diverse health‐promoting properties, such as capsaicinoids, flavonoids, phenols, carotenoids, ascorbic acid (AsA), and tocopherols. Due to this diversity and abundance of phytochemical compounds, the role of hot pepper consumption in reducing mortality has been recently acknowledged (Chopan & Littemberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical profile of this spice is characterized by the presence of molecules belonging to several chemical groups, acknowledged for their antioxidant activity (Zhuang, Chen, Sun, & Cao, ), with diverse health‐promoting properties, such as capsaicinoids, flavonoids, phenols, carotenoids, ascorbic acid (AsA), and tocopherols. Due to this diversity and abundance of phytochemical compounds, the role of hot pepper consumption in reducing mortality has been recently acknowledged (Chopan & Littemberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Capsaicinoids have attracted a great deal of attention in recent years due to their proven strong pharmacological properties. They can be used in pain relief, cancer prevention and weight reduction, and they also have gastrointestinal and cardiovascular benefits [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Going beyond the ability of spices to act as flavoring and antimicrobial agents [2], our studies show the broad-spectrum benevolence of spices through analysis of empirical data. Recent studies have shown the potential benefits of consumption of spices such as chillies through cohort studies [44] as well as the role of specific spice phytochemicals in their health effects [45]. Interestingly, the broad-spectrum benevolence score of a spice was not positively correlated with its phytochemical repertoire (S2 Fig) suggesting that richness in the phytochemical content itself does not explain its therapeutic value.…”
Section: Discussionmentioning
confidence: 99%